The Trends of Eezham Tamil Video Songs - Raguram, S.; Pirainila, K. (Proceedings of the 4th Jaffna University International Research Conference (JUICe2018), 2018)
Cinema is not only considered as a form of art but also a mode of entertainment by the general public and it is a means to spend time with pleasure, it is deeply rooted in the community without any questions. As being a visual language, scenes, frames, parts and compilations make the structure of a cinema. Cinema is a media system to tell a story through the aforementioned components and this is called the language of cinema. Video songs are also seen as the expressive dimension of the cinema. It is an expression where a director couriers the matter that he/she wanted to convey through the combination of scenes and music. It became very popular among visual media such as Television and well received by communities despite their social status. In the recent past prevalence of such songs are increasing and influence the youth very much. There is a necessity to identify the form and trends of this newly emerging visual creation. To explore the identified research questions, this is systematic research, a sample of 27 video songs released from the period between 2011 and 2016 was used as the sample. Identifying the trends of subject matters handled in video songs and identifying positives and negatives that exist for the creators of these video songs were the objectives of this study. To bring the results, this study was conducted as quantitative research with content analysis. Here the scope, the lyrics, music, scenery for the song and acting of video songs were considered. Data obtained from persons interested in video songs, directors, literature interested persons and musicians through interviews and focus group discussion were analyzed. It is revealed that the trends of video songs are impacted by war, popularity, heroism and love. Further, the video songs contain proper sound, video and other technical aspects. When it comes to the cinematography of video songs, the structure, coordination, model and different scenery; a step-by-step growth is observable in these aspects. Even though the video songs produced at the initial stages concentrated on local matters; in the recent past violence and heroism becoming the theme of video songs since recent past. Also, the study points out that the South Indian Cinema influences are clearly observable in video songs being produced in Sri Lanka.
Keywords: Video Songs; Visual Field; Creator; Trends